Medication reviews by emergency department pharmacists in patients hospitalised for an adverse drug event: a cost study - Rehana N. Rahman; Suzanne Polinder; Bojan Nikolik; Amber E. Hoek; Marjo J. A. Janssen; Stephanie C. E. Schuit; Patricia M.L.A. van den Bemt; Fatma Karapinar-Çarkit (BMC, 2024)
Abstract Objective To perform a cost study of pharmacist-led medication reviews in patients with an acute hospitalization for adverse drug events. Method Emergency department pharmacists performed medication reviews in patients hospitalized after visiting the emergency department for an adverse drug event (ADE). Control patients were hospitalized after an emergency department visit not related to an ADE and received usual care. The costs of the intervention were labour costs of the junior emergency department pharmacist and the cost savings consisted of costs of medication that was stopped or reduced during six months after the intervention. Sensitivity analyses were performed to evaluate different scenarios. Results In the intervention group (n = 104) 113 medication changes led to stopping or reducing medication, accounting for averted costs of €22,850. In the control group (n = 112) 39 medication changes led to stopping or reducing medication, accounting for averted costs of €299. The mean labour costs of the intervention were €138 per patient, resulting in saved costs of €61 per patient per six months. Sensitivity analyses showed that if the intervention would be performed by a senior clinical pharmacist, there are no cost savings (€-21), if parts of the intervention would be executed by pharmacy technicians (e.g. administrative tasks), cost savings would be augmented to €87, if outliers in costs associated with medication reduction would be excluded, there are no cost savings (€-35) and if the costs of reduced medication were extrapolated to one year, cost savings would be €260. Conclusion In this study, medication reviews by junior emergency department pharmacists in patients hospitalized after an emergency department visit for an ADE lead to a cost reduction over a six month period. Trial registration The main study is registered on the ISRCTN registry with trial ID ISRCTN12506329 on 06-03-2022.